68Ga-PSMA PET/MRI for the diagnosis of primary and biochemically recurrent prostate cancer: A meta-analysis. Issue 130 (September 2020) - Wang, Rang; Shen, Guohua; Yang, Ruoning; Ma, Xuelei; Tian, Rong
Highlights: 68 Ga-PSMA PET/MRI is an effective method in detecting prostate cancer. Detection rate increased with PSA levels in patients with biochemical recurrence. 68 Ga-PSMA PET/MRI is useful in patients even at low PSA levels. Abstract: Purpose: Our meta-analysis aimed to evaluate the diagnostic performance of 68 Ga-labelled prostate-specific membrane antigen ligand positron emission tomography/magnetic resonance imaging ( 68 Ga-PSMA PET/MRI) in patients with primary and biochemically recurrent prostate cancer (PCa). Methods: We searched for relevant articles in PubMed, EMBASE, the Cochrane Library and Web of Science until September 12, 2019. Studies regarding the diagnostic performance of 68 Ga-PSMA PET/MRI in detecting primary PCa and biochemical recurrence (BCR) after definitive treatment were included. The quality of each study was assessed using the Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2) tool. The pooled sensitivity and specificity of PET/MRI in identifying primary PCa and the pooled detection rate of PET/MRI for BCR were calculated using a random-effects model. Results: A total of 13 studies with 707 patients were included in the analysis, and the pooled sensitivity and specificity of PET/MRI in detecting primary PCa were 0.83 (95 % CI, 0.73–0.90) and 0.81 (95 % CI, 0.61–0.93), respectively. In the pooled analysis of BCR, the pooled detection rate was 76 % (95 % CI, 72 %–79 %). For four levels of PSA (0−0.2 ng/mL, 0.2−1 ng/mL, 1−2 ng/mL and more than 2 ng/mL), the pooled detection rates were 38 %, 67 %, 74 %, and 95 %, respectively. There was no distinct publication bias, but there was significant study heterogeneity. Conclusions: 68 Ga-PSMA PET/MRI is likely an effective imaging method in the diagnosis of primary PCa. In addition, the diagnostic accuracy of 68 Ga-PSMA PET/MRI in patients with BCR was also high, positively correlating with PSA levels.